Two new species and key to six species of the genus Taipodisma Yin, Zheng & Yin, 2014 from Taiwan, China (Orthoptera, Acridoidea, Catantopidae, Podisminae) - Zheng, Fang-Qiang; Shi, Jian-Ping; Dang, Yan (Zootaxa, 2016)
Two new species of the genus Taipodisma Yin et al, 2014 from Taiwan, China are described in this paper. The new species Taipodisma viriditibia sp. nov. is similar to Taipodisma hsiehi Yin et al., 2014, it differs from the latter by antennae longer, length of a middle segment 4.0 times its width; interspace of mesosternum longer in male, the length 2.0 times the narrowest; lateral lobes of metasternum slightly separated in male; epiproct of male with longitudinal sulcus at base only and length of subgenital plate of female longer than width. The new species Taipodisma kaohsiungensis sp. nov. is similar to Taipodisma nigritibia Yin et al., 2014, it differs from the latter by prozona of pronotum 1.2 times metazona; length of interspace as long as the narrowest in mesosternum of male; hind tibia yellowish green on lower side and length of subgenital plate longer than width in female. The type specimens are deposited in the National Museum of Natural Science, Taichung, Taiwan, China and the Institute of Entomology, Taiwan University, Taibei, Taiwan, China, respectively.